Deep Time Dreaming : Uncovering Ancient Australia. - Griffiths, Billy (Schwartz Publishing Pty, Limited, 2018)
--Soon after Billy Griffiths joins his first archaeological dig as camp manager and cook, he is hooked. Equipped with a historian's inquiring mind, he embarks on a journey through time, seeking to understand the extraordinary deep history of the Australian continent.--Deep Time Dreaming------. He is a research fellow at the Alfred Deakin Institute for Citizenship and Globalisation.